EKSPRESI HASIL GABAH DAN ANALISIS LINTASAN BEBERAPA VARIETAS UNGGUL BARU PADI DI SLEMAN - Bambang Sutaryo (Pusbindiklat - LIPI, 2014)
Experiments to examine the expression of grain yield and path analysis of several new rice varieties were conductedat irrigated paddy fields, Godean, Sleman, Yogyakarta, during the wet season from November 2012 to March 2013. Five new varieties of rice namely Inpari 4, Inpari 7, Inpari 10, Inpari 11 and Inpari 19 and a popular variety Ciherang were used as checks. Fifteen-day old seedlings sown one seed per hill were planted by jajar legowo 4:1 method, with spacing between plants 25cm x 12.5cm x 50cm, in a 4m x 5m plot. The experiment was designed using a randomized block pattern with three replications. Data obtained indicated that the highest grain yield was obtained by Inpari 10 (9.3 t/ha), followed by Inpari 4, Inpari 7, Inpari 11 and Inpari 19 (9.0 ; 8.6; 8.4 , and 8.3 t /ha, respectively). Those five varieties above mentioned gave grain yield significantly higher than that of Ciherang (5.5 t/ha) and provided excess grain yield amounted to 69.1; 63.6; 56.4; 52.7; and 50.9% for Inpari 10, Inpari 4, Inpari 7, Inpari 11 and Inpari 19, respectively. Maturity varies from 117 days to 122 days for Inpari 4 to Inpari 11, while the lowest plant height was 103.2 cm for Ciherang and Inpari 4 was the highest at 116.2 cm. Path analysis showed that filled grain per panicle directly affected yield, and contributed indirectly to the correlation between yield and each yield components.